A catalogue of losses for a high power, high intensity accelerator. (18th July 2014) - Nghiem, P.A.P.; Chauvin, N.; Comunian, M.; Oliver, C.; Uriot, D.
Abstract For a Megawatt class accelerator, classical safety measures may not be sufficient. Precise knowledge of beam loss location and power deposition in the most various scenarios is crucial for the definition of appropriate protection systems. In this work, the case of the Linear IFMIF Prototype Accelerator is studied, where, due to its very high continuous wave beam intensity, the high power part concerns almost the whole accelerator. Beam dynamics simulations are performed to allow the ability to estimate beam losses in all the different situations of the accelerator lifetime: starting from scratch, beam commissioning, tuning or exploration, routine operation, sudden failures. All the results of these studies are given, establishing the catalogue of losses. Recommendations for hot point protection, beam stop speed, beam power limitation are given accordingly.